2020
DOI: 10.3390/jcm9123968
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against Protein Phosphatase Magnesium-Dependent 1A as a Biomarker for Predicting Radiographic Progression in Ankylosing Spondylitis Treated with Anti-Tumor Necrosis Factor Agents

Abstract: Background: Patients with ankylosing spondylitis (AS) have increased levels of protein phosphatase magnesium-dependent 1A (PPM1A) and autoantibodies. We evaluated the usefulness of serum anti-PPM1A antibodies as a biomarker for AS. Methods: Serum samples from 58 AS patients were obtained from a multicenter registry prior to the initiation of anti-TNF agents. The serum levels of anti-PPM1A antibodies were measured using ELISA. Spinal radiographic progression was defined as an increase in the modified stoke anky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(39 reference statements)
2
5
0
Order By: Relevance
“…We previously reported that exogenous PPM1A treatment promotes matrix mineralization in AS‐osteoprogenitor cells 18 . In consistent with the previous reports, exogenous PPM1A treatment significantly enhanced matrix mineralization of AS‐osteoprogenitor cells (Figure 2A‐C).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…We previously reported that exogenous PPM1A treatment promotes matrix mineralization in AS‐osteoprogenitor cells 18 . In consistent with the previous reports, exogenous PPM1A treatment significantly enhanced matrix mineralization of AS‐osteoprogenitor cells (Figure 2A‐C).…”
Section: Resultssupporting
confidence: 92%
“…Our study focused on bone formation in AS with elevated serum PPM1A levels 16 . As a result, exogenous PPM1A treatment increased matrix mineralization in human AS‐osteoprogenitor cells suggesting PPM1A could be a serum biomarker for excessive osteoblast differentiation in AS 18 . Functionally, PPM1A has been reported to dephosphorylate AMPK or transforming growth factor beta (TGFβ) and BMPs‐activated smad1/2/3/5 proteins 10,12,14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AS mostly presents before the age of 45. Although AS has no known specific cause, individuals harbouring HLA-B27 (one among hundreds of different forms the HLA-B gene) are at a much greater risk ( 9 , 10 ). The molecular pathogenesis is complex and involves genetic, immunological, microbial (e.g., high abundance of Klebsiella pneumoniae in the gut microbiome) and hormonal (e.g., sex hormone disturbance, glucocorticoid deficiency) components ( 11 ).…”
Section: Introductionmentioning
confidence: 99%